SAT0085 Levels of CD19+ cells and IGM as predictors of an early and maintained response to rituximab in rheumatoid arthritis patients. (23rd January 2014) - Diaz-Torne, C.; Ortiz, M.A.; Geli, C.; Corominas, H.; de Llobet, J.M.; Castellví, I.; Canto, E.; Perez, E.; Juarez, C.; Casademont, J.; Diaz-Lopez, C.; Vidal, S.
Abstract : Background: Identifying predictors of response to biological agents is important for both the individual patient and health economics. There is data about several predictors of rituximab response, like a positive anti-CCP or rheumatoid factor, a low number of preplasma cells or lymphocites or an IgG level above normal.Defining response in rituximab treated patients can be complex. If we consider to measure the response to rituximab after three months, those patients with slow response will be missed. Otherwise, if we consider to measure it after six months, those ones that respond early but relapse before six months, will be also missed. Nowadays with all the current therapeutic targets, we should expect to achieve a early and maintained response. We therefore decided to consider as responders those patients that achieved a moderate/good Eular response at three and six months. Objectives: To determinate new predictors of an early and mantained response to rituximab in rheumatoid arthritis pacients. Methods: Prospective study of twenty seven consecutive rheumatoid arthritis patients, that failed to anti-TNF therapy, and were treated with rituximab (2 x 1g, two weeks apart). Demographic, clinical and laboratory data was obtained. According to our response criteria, we determined the percentage of patients who achieved an Eular response at three and six months. We then compared the baseline characteristics between early and maintained response patients (E&M-R) and the remaining patients (P). Results: Baseline characteristics: mean age was 60.2±11.2 years, 92.6% were women, RA years of evolution were 16.2 (2-35), 96.3% were seropositive (RF and/or anti-CCP), 44.4% had a history of rheumatoid nodules, 88% had an erosive RA, previous DMARDs were 3.1±1.3, previous anti-TNF were 1.45 (1-3) and DAS28 was 5.8±0.87. When comparing the clinical characteristics of E&F-R and P groups, similar DAS28 was observed. The analysis of the laboratory parameters is shown in Table . Conclusions: High absolute numbers of CD19+ cells and low IgM levels at baseline were statistically associated with an early and maintained response to rituximab. These parameters could therefore be used as predictor markers of the response. Disclosure of Interest: None Declared